The costs of data localisation: Friendly fire on economic recovery - Matthias Bauer; Hosuk Lee-Makiyama; Erik Van der Marel; Bert Verschelde (European Centre for International Political Economy (ECIPE), 2014)
This paper aims to quantify the losses that result from data localisation requirements and related data privacy and security laws that discriminate against foreign suppliers of data, and downstream goods and services providers, using GTAP8. The study looks at the effects of recently proposed or enacted legislation in seven jurisdictions, namely Brazil, China, the European Union (EU), India, Indonesia, South Korea and Vietnam. Access to foreign markets and globalised supply chains are the major sources of growth, jobs and new investments - in particular for developing economies. Manufacturing and exports are also dependent on having access to a broad range of services at competitive prices, which depend on secure and efficient access to data. Data localisation potentially affects any business that uses the internet to produce, deliver, and receive payments for their work, or to pay their salaries and taxes. (...)
Keywords: 330